Desafios da universidade pública na hipermodernidade - Martelli, Carla Gandini Giani [UNESP] (My University, 2013)
This article supposes that the Brazilian public university has dilemmas and challenges due to a more complex process that affects the whole society: Brazil has to deal with specific problems of its modernization process, at the same time that it is under pressure by the new challenges that are resulted from the globalization process. Based on a specialized literature, the aim of this article is to show how this interweaving modern/hypermodern process is challenging Brazilian public university toward more and more complex and diversified demands.

Este artigo parte do pressuposto de que os dilemas e desafios por que passa a universidade pública brasileira são resultados de um processo mais amplo que atinge toda a sociedade: o Brasil tem que lidar com problemas específicos derivados de seu processo de modernização, ao mesmo tempo em que está pressionado pelos novos desafios que advém do processo de globalização hipermoderna. Num diálogo com a bibliografia especializada, o artigo tem como objetivo mostrar como essa imbricação moderno/hipermoderno coloca a universidade pública brasileira diante de demandas cada vez mais complexas e diversificadas.
Challenges of brazilian public university in the hypermodernity
Keywords: Public University; Globalization; Hypermodernity; Bologna process; Universidade pública; Globalização; Hipermodernidade; Processo de Bolonha